2016
DOI: 10.1097/rct.0000000000000405
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Fluorine 18 Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography for Prediction of Microvascular Invasion in Small Hepatocellular Carcinoma

Abstract: F-FDG PET-CT and AFP-L3 may be useful for predicting MVI in small HCC, and the combination of the 2 factors provided reliable assessment for selection of suitable hepatic resection and liver transplantation candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 32 publications
3
25
1
Order By: Relevance
“…A radiomics nomogram to predict microvascular invasion risk in HBV-related HCC • 125 In the present study, presence of nonsmooth tumor margins, hypoattenuating halos, and internal arteries was significantly associated with MVI status in the training and validation cohorts, which is in agreement with the results of previous studies (29)(30)(31)(32). A previous study reported radiogenomic venous invasion (RVI), which included internal arteries, hypodense halo, and tumor-liver difference, as a contrast-enhanced CT biomarker for prediction of MVI (13).…”
Section: Discussionsupporting
confidence: 91%
“…A radiomics nomogram to predict microvascular invasion risk in HBV-related HCC • 125 In the present study, presence of nonsmooth tumor margins, hypoattenuating halos, and internal arteries was significantly associated with MVI status in the training and validation cohorts, which is in agreement with the results of previous studies (29)(30)(31)(32). A previous study reported radiogenomic venous invasion (RVI), which included internal arteries, hypodense halo, and tumor-liver difference, as a contrast-enhanced CT biomarker for prediction of MVI (13).…”
Section: Discussionsupporting
confidence: 91%
“…As such, in order to facilitate its inclusion into the selection process, a wide variety of studies are focused on optimizing methods of preoperative prediction of microvascular invasion using imaging modalities and other pre-transplant factors27282930404142. The results of the present study confirm that a combination of morphological tumor characteristics with serum alpha-fetoprotein concentration may be used for this purpose with moderate accuracy.…”
Section: Discussionsupporting
confidence: 57%
“…Due to the problem of intratumor heterogeneity, analysis of biopsy samples is inadequate for evaluation of microvascular invasion27. Several radiological studies have brought promising results, yet still either insufficient to provide a method of setting a definite pre-transplant diagnosis or requiring further validation27282930. Importantly, microvascular invasion is continuously reported to be associated with macroscopic tumor features, such as number and size, and serum oncologic markers31323334.…”
mentioning
confidence: 99%
“…However, the low sensitivity of 18 F‐FDG PET‐CT for detection of primary HCC was a major concern in the prestudy planning. In particular, well‐differentiated and early HCC may not be detected using FDG‐PET …”
Section: Discussionmentioning
confidence: 99%
“…In particular, well-differentiated and early HCC may not be detected using FDG-PET. 12,35 Yamashita et al 4 demonstrated that not only the presence of microinvasion such as portal venous, hepatic vein, bile duct infiltration, but also the presence of intrahepatic metastasis (satellites) is the best indicator of a poor prognosis after HR and transplantation.…”
Section: Discussionmentioning
confidence: 99%